Sonodegradation of Sulfamethoxazole in Water Using Red Mud and Rice Husk Biochar Catalysis - Thi Mai, Nguyen; Van Thanh, Dang; Manh Khai, Nguyen; Thi Minh Hang, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2024)
This research evaluated the effectiveness of sulfamethoxazole (SMX) antibiotic degradation in aqueous solution using red mud and rice husk biochar (RMC) as catalytic material for ultrasound-supported degradation process. Transmission Electron Microscopy (TEM), X-ray diffraction (XRD), and Energy-dispersive X-ray spectroscopy (EDX) were applied to study the characteristics of the catalytic material. The results demonstrated that the main components of RMC catalytic material are C, O, Si, and Fe elements with high weight percentage of 26.56%, 50.89%, 1.86% and 10.26%, respectively, and with high crystallized mix ratio. These are beneficial for SMX degradation reactions in water under the effect of ultrasound irradiation. The SMX degradation products were analyzed using High-performance liquid chromatography (HPLC). The effect of pH, contact time, initial concentration, and catalyst weight on degradation effectiveness were also investigated. The highest degradation efficiency of 75% at the treated rate of 15 mg SMX/g RMC was observed at pH = 3, contact time of 180 minutes, initial concentration of 20 mg SMX/L. This suggested a new solution to utilize the waste resources for waste treatment.